Women’s Attitudes Toward Invasive and Noninvasive Testing When Facing a High Risk of Fetal Down Syndrome - Seror, Valerie (JAMA Netw Open, 2019)
IMPORTANCE: Noninvasive prenatal testing (NIPT) using cell-free DNA in maternal blood is increasingly common compared with invasive testing (IT) in routine antenatal detection of Down syndrome (DS). OBJECTIVE: To assess attitudes and decision making in pregnant women facing a risk of fetal DS greater than 1 in 250 as established by combined first trimester screening at 11 to 14 weeks of gestation. DESIGN, SETTING, AND PARTICIPANTS: Survey study in which data were collected from pregnant women at high risk of fetal DS participating in a randomized clinical trial. Data were collected from April 8, 2014, to April 7, 2016, in 57 prenatal diagnosis centers in France. Data were analyzed in 2018. INTERVENTIONS: Data on attitudes were collected prior to offering randomization between NIPT and IT, whereas data on decision making and test results were collected as part of the clinical trial. MAIN OUTCOME AND MEASURES: The primary outcome related to attitudes. A hierarchical cluster analysis was conducted to identify clusters with contrasting attitudes. Logistic regression analyses were used to identify factors associated with attitudes. RESULTS: All 2436 consecutive women to whom the study was proposed (mean [SD] age, 36.3 [5.0] years) answered the questionnaire: 515 (21.1%) expressed preference toward IT with complete karyotyping, whereas 1843 (75.7%) favored NIPT with almost certain but limited information. Hierarchical cluster analysis yielded 4 different clusters that mainly differed in attitudes toward risk taking and extent of information seeking. Factors likely associated with attitudes driven by risk aversion were mostly age and religious beliefs (adjusted odds ratio [aOR], 1.03; 95% CI, 1.00-1.05; P = .03 and aOR, 1.62; 95% CI, 1.29-2.04; P < .001, respectively), whereas higher nuchal translucency measurements by ultrasonography were associated with attitudes driven by ambiguity aversion (aOR, 1.67; 95% CI, 1.27-2.20; P < .001). For attitudes involving both risk and ambiguity aversion at different extents, lower education was associated with highly valuing all possibilities of getting information on pregnancy, whereas higher education was associated with highly valuing information on fetal DS as a primary concern (aOR, 0.54; 95% CI, 0.44-0.67; P < .001 and aOR, 1.44; 95% CI, 1.20-1.74; P < .001, respectively). In all, decision making was in line with attitudes. CONCLUSIONS AND RELEVANCE: Aversion to risk of fetal loss related to IT and aversion to ambiguity generated by incomplete information from NIPT played a major role in shaping attitudes and decision making. Informed decision making should require pregnant women at high risk of DS to receive extensive information on targeted abnormalities by both tests.